1999
DOI: 10.1093/jmedent/36.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Study of Species Formerly Identified asAnopheles mediopunctatusand Resurrection ofAn. costai(Diptera: Culicidae)

Abstract: Anopheles (Anopheles) mediopunctatus (Lutz) and Anopheles (Anopheles) costai Fonseca & Ramos are redescribed with illustrations of the male genitalia and larval and pupal stages. The pupa of An. costai has paired lateral projections on the wing case, a feature also known in members of the Umbrosus Group from Southeast Asia. An. costai is resurrected from the synonymy of An. mediopunctatus based on features of the male genitalia, larva, and pupa, and An. bonneorum Fonseca & Ramos (emended from bonnei) is consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
0
19
0
1
Order By: Relevance
“…mediopunctatus s.l. Theobald, 1903 (now a complex of three species - Sallum et al 1999) and An. triannulatus (Neiva and Pinto, 1922) are considered to be potentially regional vectors (Arruda et al 1986, Tadei et al 1988, Deane 1988, Lourenço-de-Oliveira et al 1989, Klein et al 1991, Branquinho et al 1996 and, more recently, An.…”
mentioning
confidence: 99%
“…mediopunctatus s.l. Theobald, 1903 (now a complex of three species - Sallum et al 1999) and An. triannulatus (Neiva and Pinto, 1922) are considered to be potentially regional vectors (Arruda et al 1986, Tadei et al 1988, Deane 1988, Lourenço-de-Oliveira et al 1989, Klein et al 1991, Branquinho et al 1996 and, more recently, An.…”
mentioning
confidence: 99%
“…It was described by FONSECA & RAMOS, in 1939 6 based on specimens collected in São Vicente municipality, São Paulo State. Recently, SALLUM et al 15 8,9 showed that specimens of An. costai that were misidentified as An.…”
Section: Resultsmentioning
confidence: 99%
“…Because we collected only adult females, it was not possible to identify the specimens correctly. According to Sallum et al (1999) and Wilkerson and Sallum (1999), it is necessary to examine characteristics of the immature stages and male terminalia to discriminate among Anopheles costai, Anopheles forattini and An. mediopunctatus.…”
Section: Discussionmentioning
confidence: 99%